2013
DOI: 10.1007/s00244-013-9944-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Triphenyltin Hydroxide to Fish

Abstract: Triphenyltin (TPhT) is used worldwide in pesticide formulas for agriculture. Toxic effects of this compound to aquatic life have been reported; however, the biochemical response of fish exposed to different concentrations of TPhT hydroxide (TPhTH) was investigated for the first time in this study. The lethal concentration (LC50) of TPhTH to silver catfish, Rhamdia quelen, was calculated from an acute-exposure experiment (96 h). In addition, acethylcholinesterase (AChE) activity in brain and muscle-as well as g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
2
1
1
Order By: Relevance
“…However, scaling the elimination rate constant with volumetric length also requires that the relation between the effective area for exchange and the surface L 2 is comparable among species. For instance, in fish, the gill area is probably much larger than predicted from a scaling of arthropods based on volumetric length, which might help to explain that fish LC 50 values reported for TPT were lower than (Jarvinen et al, 1988) or comparable to (Antes et al, 2013) the toxicity values found for smaller sized arthropods in our study and elsewhere. Furthermore, body lipid content may play a role in toxicokinetics as TPT is highly lipophilic (log K OW of 3.53) and is taken up rapidly (Arnold et al, 1997).…”
Section: Prediction Of Interspecies Variationcontrasting
confidence: 61%
“…However, scaling the elimination rate constant with volumetric length also requires that the relation between the effective area for exchange and the surface L 2 is comparable among species. For instance, in fish, the gill area is probably much larger than predicted from a scaling of arthropods based on volumetric length, which might help to explain that fish LC 50 values reported for TPT were lower than (Jarvinen et al, 1988) or comparable to (Antes et al, 2013) the toxicity values found for smaller sized arthropods in our study and elsewhere. Furthermore, body lipid content may play a role in toxicokinetics as TPT is highly lipophilic (log K OW of 3.53) and is taken up rapidly (Arnold et al, 1997).…”
Section: Prediction Of Interspecies Variationcontrasting
confidence: 61%
“…The authors found that short term exposures affected primarily mayfly and caddisfly species, whereas long term exposure had chronic toxic effects on mayflies. Qi et al Antes et al (2013). LC50 values were conducted for acute toxicity and 9.73 µg L-1 was recorded, while metabolic disturbances were recorded for chronic toxicity exposure of TPhT.…”
Section: Developmental and Reproductive Toxicitymentioning
confidence: 99%
“…Triphenyltin hydroxide (TPhTH, Figure ), also known as fentin hydroxide, is used worldwide in pesticide formulas for agriculture . Metabolic alterations occurred in silver catfish juveniles ( Rhamdia quelen ) due to exposure to TPhTH even at low concentrations (1–2 μg kg −1 ) . These OTPs can contribute to farmland organotin pollution, and enter the food chain by accumulation in different plants destined for human consumption, posing a potential danger to human health.…”
Section: Introductionmentioning
confidence: 99%